Hope at dawn - Henrie, Stacy (Henrie, Stacy. Of love and war, 2014)
"With her brothers away fighting the Great War overseas, Livy Campbell desperately wants to help her family. Her chance comes when she meets a handsome stranger who lands her a job as a teacher in a place far from her parents' farm. But the war casts a long shadow over the German-American town that Livy now calls home--and the darkness will test everything she thought she knew about family and love...More than anything, Friedrick Wagner wants to be part of his adopted country's struggle for peace. But when the bitter animosity between Germans and Americans soon turns citizens against newcomers, friend against friend, he will do whatever it takes to protect Livy from the hysteria that grips their town. As tragedy--and dark secrets from the past--threaten their future, Friedrick and Livy have one chance to stand up for what's right...and one chance to fight for their love."--P. [4] of cover.